Pengaruh Kepemilikan Pemerintah, Strategi Bisnis, dan Good Coprorate Governance Terhadap Kinerja Perusahaan - Ferry Hendro Basuki (Kajian Akuntansi, 2020)
This study aims to examine the effect of government ownership, business strategy, and good corporate governance on company performance. This study uses a quantitative approach. The population in this study is state-owned companies listed on the Indonesia Stock Exchange. Determination of the sample is done by method purposive sampling and obtained 10 companies. The results showed (1) government ownership affects company performance, (2) business strategy does not affect company performance, (3) good corporate governance affects company performance.Keywords: Government Ownership, Business Strategy, Good Corporate Governance, Company Performance